DEVELOPMENT OF ELECTRICAL INSTALLATION TRAINER MEDIA WITH ADDITIONAL MEDIA HEIGHT FOR LAB EXPERIMENTS - Muhammad Aulia Rahman Sembiring; Jongga Manullang; Lia Maharani Lubis; Denny Haryanto Sinaga; Harvei Desmon Hutahaean (Jurnal Scientia, 2023)
In order to provide more realistic and pleasant electrical installation trainer media for more effective practice, researchers have developed media with an extra media height for lab tests. This study makes use of feasibility analysis and experimental techniques. An alternative that was more comfortable and efficient for learning electrical installations was the electrical installation trainer with additional media height, according to research done with students who used the trainer before height was added. The research also revealed that increasing the media height in the electrical installation trainer had an impact on the quality of the lab experiment results.